Does the DASH diet lower blood pressure by altering peripheral vascular function? - Hodson, L; Harnden, K; Roberts, R; Dennis, A; Frayn, K (2010)
We tested whether lowering of blood pressure (BP) on the dietary approaches to stop hypertension (DASH) diet was associated with changes in peripheral vascular function: endothelial function, assessed by flow-mediated vasodilatation (FMD) of the brachial artery, and subcutaneous adipose tissue blood flow (ATBF). We also assessed effects on heart rate variability (HRV) as a measure of autonomic control of the heart. We allocated 27 men and women to DASH diet and control groups. We measured FMD, ATBF and HRV on fasting and after ingestion of 75 g glucose, before and after 30 days on dietary intervention, aiming for weight maintenance. The control group did not change their diet. The DASH-diet group complied with the diet as shown by significant reductions in systolic (P<0.001) and diastolic (P=0.005) BP, and in plasma C-reactive protein (P<0.01), LDL-cholesterol (P<0.01) and apolipoprotein B (P=0.001), a novel finding. Body weight changed by <1 kg. There were no changes in the control group. We found no changes in FMD, or in ATBF, in the DASH-diet group, although heart rate fell (P<0.05). Glucose and insulin concentrations did not change. In this small-scale study, the DASH diet lowered BP independently of peripheral mechanisms.